The Ethical Responsibility of Forensic Doctors for the Confidentiality of Autopsy Results for the Crime of Murder - Andre P; Susi Delmiati; Laurensius Arliman (Master of Law Program, Ekasakti University, 2026)
The ethical responsibility of forensic doctors for the confidentiality of the results of the autopsy of the crime of murder at Bhayangkara Padang Hospital is a form of multidimensional responsibility that includes legal, ethical, social, and humanitarian aspects. In carrying out their duties, forensic doctors must maintain a balance between the obligation to assist law enforcement objectively and the protection of the dignity and privacy of victims and their families. Violations of the confidentiality of autopsy results are not only a violation of professional ethics, but also have the potential to be a violation of criminal and administrative law, which can ultimately damage the integrity of forensic institutions and public trust in the judicial system. Therefore, this responsibility must be carried out with full professional awareness, high integrity, and compliance with legal norms and noble human values. Obstacles in the implementation of the ethical responsibility of forensic doctors at Bhayangkara Padang Hospital for the confidentiality of the results of the autopsy of the crime of murder include two main dimensions, namely legal constraints and non-legal constraints. Legal obstacles include the indecisiveness of norms in Law Number 17 of 2023 concerning Health, weak structural protection for medical data, overlap between health law and criminal procedure law, and the absence of sectoral regulations that specifically regulate forensic medicine. Meanwhile, non-legal constraints include weak information security systems, low ethical literacy, social pressure on forensic doctors, lack of cross-sector training, limited support facilities, and cultural influences that sometimes do not support efforts to maintain medical confidentiality.